2019
DOI: 10.1186/s12887-019-1647-8
|View full text |Cite
|
Sign up to set email alerts
|

Associations among amino acid, lipid, and glucose metabolic profiles in childhood obesity

Abstract: Background Plasma-free amino acid profiles have been reported to correlate with obesity and glucose metabolism, and have been studied as potentially useful biomarkers of lifestyle-related diseases affecting metabolism in adulthood. However, knowledge of these relationships is lacking in children, despite the growing public health problem posed by childhood obesity. The aim of this study was to assess whether plasma-free amino acid profiles can serve as useful biomarkers of lifestyle-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
34
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 32 publications
(33 reference statements)
4
34
1
Order By: Relevance
“…BCAAs are suggested to be predictive of future T2DM (Wang et al 2011 ), and are associated with poor metabolic health (Badoud et al 2014 ; Newgard et al 2009 ). Our findings that BCAAs are higher in obese adolescents with hyperinsulinaemia/IR are consistent with previous studies in adolescents showing higher BCAAs in obese compared with lean subjects (Butte et al 2015 ; Perng et al 2014 ; Short et al 2019 ) and positive associations between BCAAs and IR (even) after adjustment for BMI (Suzuki et al 2019 ; Tricò et al 2017 ; Zhang et al 2019 ). However, data on BCAAs and metabolic health in adolescents are inconsistent (Farook et al 2015 ; Michaliszyn et al 2012 ; Mihalik et al 2012 ; Wahl et al 2012 ).…”
Section: Discussionsupporting
confidence: 92%
“…BCAAs are suggested to be predictive of future T2DM (Wang et al 2011 ), and are associated with poor metabolic health (Badoud et al 2014 ; Newgard et al 2009 ). Our findings that BCAAs are higher in obese adolescents with hyperinsulinaemia/IR are consistent with previous studies in adolescents showing higher BCAAs in obese compared with lean subjects (Butte et al 2015 ; Perng et al 2014 ; Short et al 2019 ) and positive associations between BCAAs and IR (even) after adjustment for BMI (Suzuki et al 2019 ; Tricò et al 2017 ; Zhang et al 2019 ). However, data on BCAAs and metabolic health in adolescents are inconsistent (Farook et al 2015 ; Michaliszyn et al 2012 ; Mihalik et al 2012 ; Wahl et al 2012 ).…”
Section: Discussionsupporting
confidence: 92%
“…The 10 most abundant enzyme functions were contributed from Pseudomonas including F1: histidine kinase, F2: DNA polymerase, F3: peptidylprolyl isomerase, F4: DNA helicase, F5: NADH:ubiquinone reductase (H+-translocating), F6: glutamine synthetase, F7: glutathione transferase, F8: DNA topoisomerase, F9: acetyl-CoA C-acetyltransferase, and F10: shikimate dehydrogenase in both FBT_H and FBT_S, especially for F6 and F10 functions. Shikimate dehydrogenase mainly promoted the biosynthesis of phenylalanine, tyrosine, and tryptophan, which can synthesize important neurotransmitters and hormones involved in glucose metabolism and lipid metabolism, and then regulated the blood sugar serum lipids of the human body ( Suzuki et al, 2019 ). It is known that glutamine synthetase can control the production of glutamine; interestingly, a literature reported that glutamine limitation can mitigate cancer ( Jiang et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…[17,18] Moreover, Suzuki et al found that BMI is negatively correlated with both LDL-cholesterol and total cholesterol levels in children. [19] In this study, LDLcholesterol, total cholesterol, and triglyceride levels were significantly higher in obese children than non-obese children. In addition, this study found a significant positive correlation between BMI and LDL-cholesterol, total cholesterol, and triglyceride levels.…”
Section: Discussionmentioning
confidence: 43%